A Systematic Review: Early Warning System for Hospital Wards - Sasmito, Priyo; Aljufri, Salim; Mulyati, Leli; Rasmita, Dina; Syafridawita, Yetti; Deviana, Elina; Komariah, Elis; Gayatri, Sri Wahyuni; Arifani, Nisa (PT Inovasi Pratama Internasional, 2024)
Most of the unexpected events occur in the hospital wards. An Early Warning System (EWS) is a system created to identify worsening patients outside the Intensive Care Unit (ICU). EWS is one of the requirements that must be met to get hospital accreditation. Hospitals have to choose the appropriate EWS to get optimal outcomes. This study aims to describe some of the EWS in the wards that have been researched and developed, as well as their performance in predicting severe adverse events (SAE). This study is a literature review design, conducting a systematic review by selecting relevant articles on Pub Med and Science Direct using the keyword